Climate Change and the New Polar Aesthetics : Artists Reimagine the Arctic and Antarctic - Bloom, Lisa E., 1958- (Book collections on Project MUSE., 2022)
"Climate Change and the New Polar Aesthetics considers the way artists, filmmakers, and activists use polar art to illustrate our current environmental crises as well as to reimagine our world and the ways we engage with it. Examining a wide range of contemporary art, photography, and film, Lisa E. Bloom shows how these works demonstrate the ways that our planetary crises are linked to climate change as well as a long history of colonialism and capitalism. Bloom insists on linking racial, sexual, and gendered discriminatory violence to wider environmental destruction, and she engages feminist, Black, indigenous, and non-western perspectives to address the exigencies of what we are experiencing now as the Anthropocene, or the new geological period characterized by ecosystem failures, rising sea levels, and climate-led migrations"--